The perception of Old Norse literature in modern Icelandic children’s literature - Markelova Olga (St.Tikhons' University Review. Series III. Philology, 2018)
In Icelandic children’s literature of the years 2000−2010, the texts that make use of the subjects of Old Norse literature are not very common, but their importance is undeniable. In modern culture of Iceland, the ancient literature has a high status of the “great cultural heritage” and is also extremely important in constructing the Icelandic national identity. Due to the fact that the Icelandic language has not changed considerably during the centuries, the ancient texts are read by Icelanders in the original language with comments, while younger generations may need some other ways to become familiar with the “classical” plots and characters. The modern Icelandic childern’s literature on Old Norse matters includes a great number of long and short prose texts but hardly any poems. There are mainly two genres: the mythological songs of Edda and the sagas of Icelanders (and there is also at least one example of using the kings’ sagas, namely the Saga of Ólafur Tryggvason). The texts are mainly addressed to children of the age of 9 to 13. Such children’s books have a double aim: a) the representation of the Old Norse universe itself, b) the representation of the recipient, who is supposed to be a child interested in culture and history of Iceland. Bringing the Old Norse subject to young readers can be achieved by various ways. It can be a simple retelling of a saga or a myth adapted to the perception of a modern reader. In such cases, many things concerning the realia and the worldview of the ancient age require explanation; the facts are usually never altered, even those which are not wholly in line with modern ethics. An ancient plot or person can be placed in the context of modern daily life, with e.g. Thor or Loki becoming schoolchildren. A sci-fi pattern can be employed, e.g. when a modern child finds his way into the Old Norse universum and the realm of gods. Alternativelly, a modern child can come in touch with some Old Norse realia in the modern world, such as archeological fi nds or ancient inscriptions. ...